2008
DOI: 10.1585/pfr.3.016
|View full text |Cite
|
Sign up to set email alerts
|

Particle Orbit Analysis in the Finite Beta Plasma of the Large Helical Device using Real Coordinates

Abstract: High-energy particles in a finite beta plasma of the Large Helical Device (LHD) are numerically traced in a real coordinate system. We investigate particle orbits by changing the beta value and/or the magnetic field strength. No significant difference is found in the particle orbit classifications between the vacuum magnetic field and the finite beta plasma cases. The deviation of a banana orbit from the flux surfaces strongly depends on the beta value, although the deviation of the orbit of a passing particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…When χ of ions change from 0.5π to 0.4π or 0.6π because of the collisions, the ions become chaotic-orbit particles. For the conditions used, most chaotic-orbit particles also become the re-entering particles [8]. Therefore, F LCFS (χ) is underestimated near 0.4π or 0.6π.…”
Section: Monte-carlo Study Based On Real Coordinates For Perpendiculamentioning
confidence: 99%
See 3 more Smart Citations
“…When χ of ions change from 0.5π to 0.4π or 0.6π because of the collisions, the ions become chaotic-orbit particles. For the conditions used, most chaotic-orbit particles also become the re-entering particles [8]. Therefore, F LCFS (χ) is underestimated near 0.4π or 0.6π.…”
Section: Monte-carlo Study Based On Real Coordinates For Perpendiculamentioning
confidence: 99%
“…This code has already been applied to the ions produced by the tangential-NBs in LHD, and it was shown that the re-entering particles play an important role in the analyzing the distribution function of ions author's e-mail: seki.ryohsuke@lhd.nifs.ac.jp a) present address: National Institute for Fusion Science, Toki 509-5292, Japan produced by the tangential-NBs for B ax = 3 T [3]. On the other hand, it has also been shown that most of the protons produced by the perpendicular-NB become the re-entering particles in high-beta plasmas [8]. Thus, the re-entering particles may play a more important role in the distribution function in the high-beta plasma.…”
Section: Monte-carlo Study Based On Real Coordinates For Perpendiculamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in helical devices such as the LHD, the shape of the resonance layer is more complicated than that of a tokamak. The fast ions heated by the ICRF wave become a "banana orbit particle (helical trapped particle)" [2] which forms a closed drift surface or a "chaotic orbit particle" [2] which does not form the closed drift surface depending upon the shape of the resonance layer. The shape of the resonance layer may affect the transferred power efficiency from minority fast ions to bulk plasma.…”
Section: Introductionmentioning
confidence: 99%